Birthweight of IVF children is still a current issue and still related to maternal factors. Issue 6 (December 2019) - Beltran Anzola, Any; Pauly, Vanessa; Riviere, Olivier; Sambuc, Roland; Boyer, Pierre; Vendittelli, Françoise; Gervoise-Boyer, Marie-José
Abstract: Research question: Does fresh embryo transfer after IVF with or without intracytoplasmic sperm injection (ICSI) increase the small for gestational age (SGA) rate, and frozen embryo transfer (FET) after IVF with or without ICSI increase the large for gestational age (LGA) rate versus natural conception? Design: Retrospective comparison of an exposed historical group/cohort involving singletons conceived after fresh embryo transfer and after FET with an unexposed group/cohort involving singletons conceived after a natural conception. Results: A total of 1961 fresh embryo transfer babies and 366 FET babies were compared with 6981 natural conception babies. The SGA rate in fresh embryo transfer babies was not significantly different to natural conception babies (6.9% versus 6.8%, P  = 0.856). This outcome was not influenced by the fresh embryo transfer (adjusted odds ratio [aOR] 1.0; 95% confidence interval [CI] 0.8–1.3), but rather by a low rate of multiparity (aOR 0.5; 95% CI 0.3–0.7), advanced maternal age (aOR 1.1; 95% CI 1.0–1.2), maternal underweight (aOR 1.5; 95% CI 1.1–2.1), maternal smoking or cessation during pregnancy (aOR 1.8; 95% CI 1.4–2.3), pre-existing hypertension (aOR 2.3; 95% CI 1.3–4.1) and pregnancy-induced hypertension (aOR 2.5; 95% CI 1.7–3.7). The LGA rate in FET babies was significantly different from natural conception babies (6.6% versus 3.2%, P  = 0.012). This outcome was influenced by the transfer of frozen embryos (aOR 2.2; 95% CI 1.3–3.8) and by a high maternal weight (aOR 1.9; 95% CI 1.1–3.6). Conclusions: Maternal background and obstetric parameters are more likely to influence the SGA rate than fresh embryo transfer conception. FET conception could be associated with an increase in LGA rate.